1998
DOI: 10.1183/09031936.98.11051105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slow-release theophylline on nasal antigen challenge in subjects with allergic rhinitis

Abstract: It has been recognized recently that theophylline possesses anti-inflammatory effects that could be of clinical interest in patients with airway inflammatory diseases such as asthma and allergic rhinitis (AR). The aim of the present study was to explore the effect of theophylline on the nasal eosinophilic inflammatory response following allergen challenge in patients with AR. Fourteen subjects suffering from seasonal rhinitis with an early reaction after nasal allergen provocation were challenged outside the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This challenge involved an automatic inhalation-synchronized Mefar MB3 dosimeter jet nebulizer (Mefar SpA, Bovezzo, Italy). We used the same standardized extract of five grass pollen allergens as for the skin test (Stallergenes Laboratory) The initial allergen concentration of standardized pollen extract was 0.1 or 0.2 IR (index of reactivity), as previously described by Aubier et al (1998). The concentration of inhaled allergen was doubled every 15 min; the FEV 1 was measured immediately after each doubling and again 10 min after each inhalation.…”
Section: Methodsmentioning
confidence: 99%
“…This challenge involved an automatic inhalation-synchronized Mefar MB3 dosimeter jet nebulizer (Mefar SpA, Bovezzo, Italy). We used the same standardized extract of five grass pollen allergens as for the skin test (Stallergenes Laboratory) The initial allergen concentration of standardized pollen extract was 0.1 or 0.2 IR (index of reactivity), as previously described by Aubier et al (1998). The concentration of inhaled allergen was doubled every 15 min; the FEV 1 was measured immediately after each doubling and again 10 min after each inhalation.…”
Section: Methodsmentioning
confidence: 99%
“…In a small double‐blind crossover study, treatment out of season of rhinitic patients with theophylline reduced the release of mediators from mast cells and attenuated sneezing after nasal allergen challenge [22]. Another controlled study in patients with seasonal allergic rhinitis demonstrated that treatment with theophylline reduced symptoms, nasal obstruction, eosinophils influx and ECP concentration in nasal lavage fluid after nasal allergen challenge [23]. Similar studies with topical corticosteroids found an effect on nasal obstruction of the same order of magnitude.…”
Section: Adenosine Signalling In Allergic Rhinitis?mentioning
confidence: 99%